The Association between Maternal Factors and Preterm Birthand Premature Rapture of Membranes - Zohreh Mahmoodi; Fatemeh Hoseini; Homa Avval Shahr; Zahra Ghodsi; Leila Amini (Tehran University of Medical Sciences, 2010)
Objective: The aim of this study was to estimate the frequency of preterm birth (PTB) and premature rapture of membranes (PROM) and their associations with maternal factors. Material and methods: This cross sectional study was carried out at Akbar-Abadi hospital in Tehran during January 2009-Aprile 2010. Four hundred sixty six primiparous women with gestational age more than 20 weeks and singleton pregnancy were enrolled in the study. Data were analyzed using SPSS-16. P<0.05 was considered as being significant. maternal age, maternal height ,maternal education, pre- pregnancy maternal weight, occupation and smoking during pregnancy were compared between two groups (with or without PTB/PROM). Results: This study shows the incidence of PTB to be 27.9% and PROM to be 34.7%. None of maternal factors in this study showed significant relation with PTB. Significant relation was found between maternal age and PROM, p<0.001. PROM was related to PTB significantly (p=0.040). Conclusion: Findings highlighted the importance of maternal age as a cause of adverse pregnancy outcomes. Since this study showed PROM and PTB to be two common adverse pregnancy outcomes in Iran assembling appropriate services can lead mothers to improved pregnancy outcomes especially among older pregnant women.